Type I interferon in the pathogenesis of systemic lupus erythematosus. (December 2020) - Postal, Mariana; Vivaldo, Jessica F; Fernandez-Ruiz, Ruth; Paredes, Jacqueline L; Appenzeller, Simone; Niewold, Timothy B
Highlights: Type I IFN is implicated in SLE pathogenesis by multiple lines of evidence, including genetics and induction of SLE by IFN treatment. Nucleic-acid sensing pathways influence the threshold of activation and triggering of type I IFN production. Abnormalities in extracellular processing of DNA can enhance type I IFN production. High type I IFN levels are associated with nephritis, mucocutaneous manifestations, and the presence of autoantibodies in SLE. Anifrolumab, a monoclonal antibody that blocks the type I IFN receptor, has shown therapeutic benefit in SLE. Abstract : Type I interferon (IFN) is a primary pathogenic factor in systemic lupus erythematosus (SLE). Gain-of-function genetic variants in the type I IFN pathway have been associated with risk of disease. Common polygenic as well as rare monogenic influences on type I IFN have been demonstrated, supporting a complex genetic basis for high IFN in many SLE patients. Both SLE-associated autoantibodies and high type I IFN can be observed in the pre-disease state. Patients with SLE and evidence of high type I IFN have more active disease and a greater propensity to nephritis and other severe manifestations. Despite the well-established association between type I IFN and SLE, the specific triggers of type I IFN production, the mechanisms by which IFNs help perpetuate the cycle of autoreactive cells and autoantibody production are not completely clear. This review provides an updated overview of type I IFN in SLE pathogenesis, clinical manifestations, and current therapeutic strategies targeting this pathway.